2013
DOI: 10.1007/s13197-013-1177-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of phenolic compound and antioxidant activity of date fruit as a function of ripening stages and drying process

Abstract: Edible parts of two varieties of date palm (Mazfati and Kalute varieties) (Phoenix dactylifera) fruits (DPF) from Iran were analyzed to determine their phenolic compound and antioxidant activities (AA). Antioxidant activity evaluated using typical methods such as 2, 2-diphenyl-1-picrylhydrazyl (DPPH), reducing power and total antioxidant method. The total phenolic content (TPC) of the DPF was measured using Folin-Ciocalteau method. The samples used in this study included samples were gathered at three stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 36 publications
3
23
0
2
Order By: Relevance
“…Moreover, anti‐HIV activity of olive leaf extract was proved by modulation of host cell gene expression by HIV‐1 infection (Lee‐Huang, Zhang, Huang, Chang, & Huang, ). The antioxidative, antimicrobial, anti‐inflammatory, antithrombotic, antihypertensive, and hypoglycemic properties of the olive leave extracts have been reported to be attributed to their bioactives such as phenolic compounds (e.g., oleuropein) (Shahdadi, Mirzaei, & Garmakhany, ). Several methods have been applied for the extraction of phenolic compounds from olive leaves and by‐products, such as pressurized liquid extraction (Xynos et al, ), microwave‐assisted extraction (Şahin et al, ), electrotechnologies (Puértolas & Barba, ), and ultrasonic‐assisted extraction (Dedousi, Mamoudaki, Grigorakis, & Makris, ; Roselló‐Soto, Galanakis, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, anti‐HIV activity of olive leaf extract was proved by modulation of host cell gene expression by HIV‐1 infection (Lee‐Huang, Zhang, Huang, Chang, & Huang, ). The antioxidative, antimicrobial, anti‐inflammatory, antithrombotic, antihypertensive, and hypoglycemic properties of the olive leave extracts have been reported to be attributed to their bioactives such as phenolic compounds (e.g., oleuropein) (Shahdadi, Mirzaei, & Garmakhany, ). Several methods have been applied for the extraction of phenolic compounds from olive leaves and by‐products, such as pressurized liquid extraction (Xynos et al, ), microwave‐assisted extraction (Şahin et al, ), electrotechnologies (Puértolas & Barba, ), and ultrasonic‐assisted extraction (Dedousi, Mamoudaki, Grigorakis, & Makris, ; Roselló‐Soto, Galanakis, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Biglari et al (2008) reported amounts that ranged from 2.89 to 6.64 mg/100 g in different genotypes of Phoenix dactylifera; Jacques et al (2009) reported an average of 328.6 mg/100 g in B. odorata and Faria et al (2008) reported amounts that ranged from 163 to 250 mg/100 g fw in B. capitata. However, Shahdadi et al (2015) observed a variation in amounts of phenols in four fruit ripening stages of Phoenix dactylifera, with values ranging from 2.89 to 4.82 mg/100 g fw in mature fruits. These compounds are essential to plant growth, reproduction and defense against Mean value ± standard deviation of fruit pulp weight; n = 3.…”
Section: Resultsmentioning
confidence: 94%
“…It is well known that the freeze‐drying method is the best technique to dehydrate foods with the best preservation of functional ingredients in foods (Garcia‐Amezquita, Welti‐Chanes, Vergara‐Balderas, & Bermúdez‐Aguirre, 2016), because many functional compounds, including phenolic compounds and antioxidants, are susceptible to oxidation, which results in a loss of their bioactive functions (Joshi, Rupasinghe, & Khanizadeh, 2011). During the freeze‐drying process, low temperature condition with the absence of oxygen could better prevent these functional elements from being oxidized (Shahdadi, Mirzaei, & Daraei Garmakhany, 2015; Shahdadi, Mirzaei, Maghsoudlou, Ghorbani, & Daraei, 2011). In the present study, all the freeze‐dried Sedum aizoon L. sample fractions exhibited the highest total flavonoids content compared to those under the oven and sun‐drying methods.…”
Section: Resultsmentioning
confidence: 99%